Analisis Pengelolaan Retribusi Sewa Peralatan dan Mesin dalam Meningkatkan Pendapatan Asli Daerah (PAD) pada Dinas Pekerjaan Umum dan Penataan Ruang (DPUPR) Kota Mataram - Novita Indah Sari; Herlina Pusparini; Yusli Mariadi (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and analyze the management of equipment and machinery rental fees in increasing PAD at the DPUPR of Mataram City. This research is qualitative research with a descriptive type. The informants in this study were 6 people who were selected based on the author's view that the informants had knowledge and information about the problem under study. The data analysis used is data collection, data reduction, data presentation, and conclusion drawing. This research uses source and technique triangulation in data validation. The results of the study concluded that the management of equipment and machine rental levies carried out by the DPUPR in increasing the PAD of Mataram City had been carried out well based on the indicators of planning, organizing, directing, and supervising. However, the acceptance of this levy is still not maximized by the potential it has due to several inhibiting factors, namely the inadequate facilities or heavy equipment due to limited budgets, then the lack of quality human resources in terms of knowledge, competition with private parties, the lack of tenants and the Covid-19 outbreak